Room temperature deep eutectic solvents of (1S)-(+)-10-camphorsulfonic acid and sulfobetaines: hydrogen bond-based mixtures with low ionicity and structure-dependent toxicity1. Issue 40 (7th May 2015) - Cardellini, Fabio; Germani, Raimondo; Cardinali, Gianluigi; Corte, Laura; Roscini, Luca; Spreti, Nicoletta; Tiecco, Matteo
<x xml:space="preserve">Abstract</x> Preparation, properties and toxicity of room temperature deep eutectic solvents formed by (1S)-(+)-10-camphorsulfonic acid and aromatic, aliphatic and amphiphilic sulfobetaines.